2001
DOI: 10.1901/jeab.2001.75-247
|View full text |Cite
|
Sign up to set email alerts
|

Response Rate Viewed as Engagement Bouts: Effects of Relative Reinforcement and Schedule Type

Abstract: The rate of a reinforced response is conceptualized as a composite of engagement bouts (visits) and responding during visits. Part 1 of this paper describes a method for estimating the rate of visit initiations and the average number of responses per visit from log survivor plots: the proportion of interresponse times (IRTs) longer than some elapsed time (log scale) plotted as a function of elapsed time. In Part 2 the method is applied to IRT distributions from rats that obtained food pellets by nose poking a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
307
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(348 citation statements)
references
References 40 publications
40
307
1
Order By: Relevance
“…As was discussed in Tanno et al (2010), if we accept Herrnstein's (1970) notion that single schedules can be viewed as a choice situation between experimentally reinforced behavior and endogenously reinforced behavior, our conclusion is consistent with findings from Shull and colleagues (Shull, 2011;Shull, Gaynor, & Grimes, 2001;Shull & Grimes, 2003;Shull, Grimes, & Bennett, 2004) in single-schedule situations. They reported that responses (or IRTs) under single reinforcement schedules can be classified into bouts of responses or pauses, and that reinforcement frequency mainly affects the start of a bout (bout-initiation rate), whereas types of reinforcement schedule (VI and tandem VI-FR or tandem VI-VR) mainly affect the speed of responding within a bout (withinbout response rate).…”
Section: Discussionsupporting
confidence: 90%
“…As was discussed in Tanno et al (2010), if we accept Herrnstein's (1970) notion that single schedules can be viewed as a choice situation between experimentally reinforced behavior and endogenously reinforced behavior, our conclusion is consistent with findings from Shull and colleagues (Shull, 2011;Shull, Gaynor, & Grimes, 2001;Shull & Grimes, 2003;Shull, Grimes, & Bennett, 2004) in single-schedule situations. They reported that responses (or IRTs) under single reinforcement schedules can be classified into bouts of responses or pauses, and that reinforcement frequency mainly affects the start of a bout (bout-initiation rate), whereas types of reinforcement schedule (VI and tandem VI-FR or tandem VI-VR) mainly affect the speed of responding within a bout (withinbout response rate).…”
Section: Discussionsupporting
confidence: 90%
“…Describing the full response distribution as a mixture of a Poisson pdf and a zero distribution is similar to other mixture-model approaches that have successfully described the distribution of response intervals in instrumental conditioning paradigms using variable-interval schedules of reinforcement (e.g., Brackney, Cheung, Neisewander, & Sanabria, 2011;Shull, Gaynor, & Grimes, 2001;Shull, Grimes, & Bennett, 2004). A notable difference between those approaches and the current one is that those approaches model behavior as a mixture of two Poisson processes, one describing high response rates (during response bouts) and the other capturing long response intervals (pauses between bouts).…”
Section: Discussionmentioning
confidence: 97%
“…We lack any theoretical account of concurrent fixed-interval-fixed-interval and fixed-intervalvariable-interval schedules. However, a recent study by Shull et al (2001;see also Shull 1979) suggests that response rate may not capture what is going on even on simple variableinterval schedules, where the time to initiate bouts of relatively fixed-rate responding seems to be a more sensitive dependent measure than overall response rate. More attention to the role of temporal variables in choice is called for.…”
Section: Concurrent-chain Schedulesmentioning
confidence: 99%